STORYTELLING AS A MARKETING COMMUNICATION STRATEGY FOR â€œPRIMADONA-FOODâ€ BEKASI - Patria, Laskarko (Bina Nusantara University, 2022)
Storytelling strategies are increasingly being used in an effort to get the attention and prospects of customers. The technique of distributing brand content, using parameters such as broadcast time, interactivity, and the type of information it conveys. Effective digital campaigns require a high level of creativity and often involve developing a storyline around the brand. The owner of a micro business, a food product with the Primadona-food brand, which initially had few customers, then, in March 2018, I directed to use a storytelling strategy in marketing on social media. This strategy has proven to be successful in increasing the number of Primadona food consumers, to reach consumers and customers overseas. The development of creativity in digital strategies also serves to foster long-term relationships and loyalty to the Primadona-food Bekasi brand, consumers interact with the brand, the higher level of brand awareness. Consumer confidence can increase, if the story is relevant to consumers, offers concrete details, engaging video or audio, and promotes positive values. The value of digital storytelling as the main tool for communicating the experience of a brand is indeed very useful in marketing activities.